Instructional strategy in the teaching of computer programming: a needs assessment analyses / Mohd Nasir Ismail, Nor Azilah Ngah and Irfan NaufalUmar - Ismail, Mohd Nasir; Ngah, Nor Azilah; Naufal, Irfan (Penerbit UiTM (UiTM Press), 2008)
The process of Instructional Design deals with the production of an effective, efficient and appealing instructional material under different condition, method and outcome. Computer programming is part and parcel of computer education. Research done in western countries has shown that programming requires problem solving and analytical thinking skill; unfortunately these skills are found to be deficient among many students pursuing computer programming courses. A needs assessment was done to identify whether such a problem exists amongst Malaysian students pursuing computer programming courses in a Malaysian university. Among others, the aim of the needs assessment is to identify the instructional problems pertaining to the current strategies used for the teaching of programming. This paper reports and discusses the findings collected from the interviews with five computer science lecturers from the faculty of computer science in a local university. The result shows that there are deficiencies in knowledge, understanding and application of computer programming among computer science students.